Notes: The “Gambler's Fallacy” in Lottery Play - Clotfelter, Charles T.; Cook, Philip J. (Management Science, 1993)
The “gambler's fallacy” is the belief that the probability of an event is lowered when that event has recently occurred, even though the probability of the event is objectively known to be independent from one trial to the next. This paper provides evidence on the time pattern of lottery participation to see whether actual behavior is consistent with this fallacy. Using data from the Maryland daily numbers game, we find a clear and consistent tendency for the amount of money bet on a particular number to fall sharply immediately after it is drawn, and then gradually to recover to its former level over the course of several months. This pattern is consistent with the hypothesis that lottery players are in fact subject to the gambler's fallacy.